Stability of Adams-type formulae for second-order ordinary differential equations - Hall, G.; Suleiman, M.B. (1981)
The stability of methods for systems of second-order equations is discussed. Stability regions are obtained for a single equation and the existence of stable step-sizes is shown for systems. An example is used as an illustration of the effect of the usual order selection strategies on stability and accuracy. © 1981, by Academic Press Inc. (London) Limited.